Developing an aviation-based syllabus for PAFU officer-cadets - Filipczuk-Rosińska Sylwia (2023)
The main objective of the following paper is to present the teaching rationale and premises underlying the development of materials and an aviation-based syllabus designed for officer-cadets of the Polish Air Force University. Additionally, as a practical illustration of implementing content-based instruction in the PAFU classroom, the gradual process underlying the personally developed tasks integrating not only contextualised grammar and vocabulary, but also receptive and productive skills was meticulously described.